The avian infectious Laryngotracheitis in Greece. II. Epizootiological data, aspect of the disease and neasures of control - ΜΕΝΑΣΕ Ι.; ΣΕΪΜΕΝΗΣ Α.; ΒΕΪΜΟΣ Γ.; ΛΟΥΚΑΣ Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
After a brief review on the history of infectious laryngotracheitis in Greece, the aithors deal with the appearance of outbreaks of the disease in an epizootic form, for the first time on 1965 in the area of Megara (Attica) and in a more severe form and extension on 1971 in the island of Eubea. The clinical and anatomopathological aspect of the disease is described, as the measures of control by vaccination adopted. The kind of vaccines distributed in the market in that time, which were prepared with a virulent strain of virus and administrated by the vent—brush merhod, are discribed. To obviate the disadvantage of creating carriers of the disease by such a method of administration, a study for the creation of a modified mild vaccine virus strain was undertaken by the Central State Veterinary Institute and a live vaccine was prepared. The use of the live virulent virus vaccines was prohibited thereafter and the new kind of vaccine widely distributed. The eye—drop method of administration was largely used and in the drinking water as well, experimentaly and in the field, giving a very satisfacrory protection. The authors conclude that, control of the disease by vaccination can give very satisfactory results provided that, beside the sanitary measures, it is systematically applied with a high quality product.